Comparison of positive expiratory pressure device versus non-invasive ventilation on outcomes in acute exacerbation of chronic obstructive pulmonary disease in the emergency department - Emine Sarcan; Ahmet Burak Erdem; Merve Yazla; Şerife Büşra Uysal; Elif Çelikel (BMC Emergency Medicine)
Abstract Background Acute exacerbations of chronic obstructive pulmonary disease (COPD) are among the most common reasons for emergency department visits. In patients who develop hypercapnic respiratory failure, non-invasive mechanical ventilation (NIV) is generally the preferred treatment. However, in overcrowded emergency departments, the number of mechanical ventilation devices may be insufficient. In such situations, positive expiratory pressure (PEP) devices can be utilized. This study aims to evaluate the clinical efficacy of the PEP device (EzPAP®) compared to NIV for the management of exacerbations of COPD in the emergency department. Methods This prospective, randomized controlled study was conducted on 103 patients who presented to the emergency department with exacerbations of COPD and acute hypercapnic respiratory failure between November 2023 and April 2024. Patients were divided into two groups: EzPAP® (E) and NIV (N). Spirometric parameters, arterial blood gas values, hospital admission rates, and 30-day mortality rates were compared before and after treatment in both groups. Results A total of 103 patients were included in the study (N: 49, E: 54). In Group N, no statistically significant increase was observed in FEV₁ and FVC after treatment (p = 0.120). A statistically significant increase in FEV₁ and FVC was detected in the EzPAP group (p < 0.001). An increase in oxygen saturation and an improvement in PaCO₂ and lactate levels were observed in both groups (p < 0.001). The difference in blood gas values before and after treatment (delta = Δ) was not statistically significant between the two groups. However, ΔFEV₁ and ΔFVC were significantly higher in the EzPAP group compared to the NIV group (p = 0.007, p = 0.022). The hospital admission rate was higher in the NIV group than in the EzPAP® group (p = 0.04). Conclusion EzPAP® may be a suitable option for use in overcrowded emergency departments, as it demonstrates efficacy comparable to NIV in the management of exacerbations in COPD. Additionally, it can also be considered as a treatment alternative in situations where the number of mechanical ventilation devices for NIV is insufficient, such as during a pandemic. Trial registration ClinicalTrials Number: NCT06561464 Registration Date: 07/08/2024.